2005
DOI: 10.1042/bj20050678
|View full text |Cite
|
Sign up to set email alerts
|

PNUTS enhances in vitro chromosome decondensation in a PP1-dependent manner

Abstract: PP1 (protein phosphatase-1) is a serine/threonine phosphatase involved in mitosis exit and chromosome decondensation. In the present study, we characterize the subcellular and subnuclear localization of PNUTS (PP1 nuclear targeting subunit), a nuclear regulatory subunit of PP1, and report a stimulatory role of PNUTS in the decondensation of prometaphase chromosomes in two in vitro systems. In interphase, PNUTS co-fractionates, together with a fraction of nuclear PP1, primarily with micrococcal nuclease-soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 33 publications
5
61
0
3
Order By: Relevance
“…Moreover, it has been observed in many organisms that the impairment of PP1 activity leads to a mitotic arrest (53)(54)(55)(56)(57). Further studies have shown that PP1 activity should be closely controlled to ensure correct centrosome separation and for the segregation/decondensation of chromosomes (6,58,59). In P. falciparum, although it has been shown that PP1 is essential for parasite survival and for the release of infectious merozoites (12,18,60,61), little is known about the expression of regulators of PP1 and on the nature of their exact functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been observed in many organisms that the impairment of PP1 activity leads to a mitotic arrest (53)(54)(55)(56)(57). Further studies have shown that PP1 activity should be closely controlled to ensure correct centrosome separation and for the segregation/decondensation of chromosomes (6,58,59). In P. falciparum, although it has been shown that PP1 is essential for parasite survival and for the release of infectious merozoites (12,18,60,61), little is known about the expression of regulators of PP1 and on the nature of their exact functions.…”
Section: Discussionmentioning
confidence: 99%
“…Classical pairs of three-dimensional HNCACB, HN(CO)CACB, HNCO, HN(CA)CO, and HN(CA)N were processed using Bruker TOPSPIN 2.1 and used for the assignment of the backbone 1 H N , 15 N, and C␣ atoms, and C␤ (supplemental Table S2). The backbone assignment is not complete due to weak signals in several regions of the protein (N terminus, Lys 58 -Lys 68 and Asp 90 -Asn 103 ). For the assignment of the PfI3W45A mutant, only an additional pair of three-dimensional HNCACB and HN(CO)CACB was necessary.…”
Section: Methodsmentioning
confidence: 99%
“…PNUTS contains several functional domains, including an N-terminal transcription elongation factor S-II (TFS2N) domain implicated in the transcriptional initiation or elongation of RNA polymerase (pol) II (19), a putative zinc finger domain, a consensus PP1-binding RVXF motif, and C-terminal RGG motifs that interact with homopolymeric RNA (17,20). PNUTS is ubiquitously expressed and tightly associates with chromatin during interphase but is excluded from chromosomes at early mitosis and is reloaded onto chromosomes during the transition from mitosis to interphase (21). PNUTS also enhances in vitro chromosome decondensation in a PP1-dependent manner.…”
Section: Protein Phosphatase 1 (Pp1)mentioning
confidence: 99%
“…The PP1 catalytic subunits are highly mobile and their subcellular localization could change with the expression levels of the targeting proteins (Trinkle-Mulcahy et al, 2001;Trinkle-Mulcahy et al, 2003). One of the major nuclear targeting subunits of PP1a and PP1c is the phosphatase nuclear targeting subunit PNUTS [also known as serine/threonine-protein phosphatase 1 regulatory subunit 10 (PP1R10) and p99] that localizes to the nucleoplasm (Landsverk et al, 2005) and can be found occasionally in CBs (Moorhead et al, 2007). These data illustrate how dynamic and transient the targeting of PP1 to different specific subcellular sites could be.…”
Section: Introductionmentioning
confidence: 99%